Métodos e técnicas de avaliação de empresas: um estudo visando à mensuração dos ativos intangíveis em empresas industriais do setor eletroeletrônico - Melo, Paulo da Silva (2009)
The thematic central office of this project is the study of the methods and techniques of evaluation of companies who can support the process of measurement of the Intangible Assets, more specifically of the projection of the potential of economic result of these aspects. The objective is to obtain to inside approach the countable information of economic of the industrial companies of the eletroeletronics sector, without its reference (historical cost) either abandoned, propitiating an additional and excellent information to the managers in the taking of decisions that they aim at to the present and to the future, in the processes of acquisitions or fusing, Through a study of in four representative companies of the sector of eletroeletronics that, it is intended to verify the utility of the application of the methods and the techniques of evaluation of companies, to contribute in the measurement of the Intangible Assets, in companies of the industrial sector of eletroeletronics. The difficulty in understanding this aspect has caused innumerable questions and quarrels regarding the importance of the countable information and the position of the accountant